UMP - The champion of MTUN Sports Championship 2011 - UMP, PNC
Universiti Malaysia Pahang (UMP) emerged as the overall champion of the 4th Inter-Technical Varsity Sports Championship which was held for four days at UMP Sports Complex in Gambang on December 18, 2011.